PESANTREN DAN PROGRAM DERADIKALISASI AGAMA - Arkanudin Budiyanto; Subejo Subejo; Samsul Maarif (UIN Raden Mas Said Surakarta, 2019)
This study tries to describe responses of the pesantren community on the deradicalization program carried out by the Indonesian government in the Sukoharjo Regency, Central Java along with various factors that influence to those responses. Through the qualitative approach, the results of studies show that pesantren have a strategic role in supporting the success of deradicalization program. Pesantren, which have been united with the community, are trusted and believed by the community as an institution capable of making changes to the outlook as well as the religious model of the community. However, the involvement of pesantren needs to pay attention based on the cultural factors that exist in the pesantren environment. This cultural frame will then be able to support the appropriate deradicalization communication patterns, and the right acceptance of the government in running the deradicalization program.